New Materials for Tunable FBAR Applications: Modelling and Fabrication - Alam Mallick, Shoaib (My University, 2012)
Electronically tunable and switchable microwave devices play a vital role in providing the adaptability to the RF system. Tunable devices enable the design of communication systems with reduced size and complexity. This thesis report describe the simulation, fabrication and characterization of an electrically tunable FBAR test structures based on BiFeO3 (BFO) and Mn‐doped (1‐x) BiFeO3–xBaTiO3 (BFBTO) thin film deposited by Pulse Laser Deposition. During the study of the BFBTO based devices it reveals that BFBTO is in ferroelectric state since it shows hysteresis effect at low frequency in agreement with theoretical studies of the BFBTO ceramics. It is found that the field induced piezoeffect in the BFO films is rather week, while an intense field induced piezoeffect is observed in the BFBTO based FBAR test structures. The resonance frequency appears at 4.6 GHz and an applied field up to 33V/μm. The effective electromechanical coupling coefficient extracted is 0.042. Tunability for the BFBTO FBAR test structure calculated through this coupling coefficient is 2% moreover measurements also indicate that increase in content of Mn reduces the loss tangent of the device. These results demonstrate that the BFBTO has high potential for applications in tunable FBAR devices.
Keywords: Keramteknik; Informations- och kommunikationsteknik; Materialvetenskap; Ceramics; Information & Communication Technology; Materials Science